2020
DOI: 10.3390/md19010010
|View full text |Cite
|
Sign up to set email alerts
|

Marine-Derived Biologically Active Compounds for the Potential Treatment of Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic, systemic autoimmune disease with a prevalence rate of up to 1% and is significantly considered a common worldwide public health concern. Commercially, several traditional formulations are available to treat RA to some extent. However, these synthetic compounds exert toxicity and considerable side effects even at lower therapeutic concentrations. Considering the above-mentioned critiques, research is underway around the world in finding and exploiting potential alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 173 publications
(240 reference statements)
0
2
0
Order By: Relevance
“…However, some patients could develop more serious problems such as a resurgence of previous infections like tuberculosis. Many concerns emerge about possible increases in cardiovascular risk and disease occurrence [ 123 , 124 ]. It is obvious from these conventional treatment options that a more sustainable, much safer, and perhaps food-derived alternative therapy is warranted for treating or managing RA.…”
Section: Conventional Treatment Of Ramentioning
confidence: 99%
“…However, some patients could develop more serious problems such as a resurgence of previous infections like tuberculosis. Many concerns emerge about possible increases in cardiovascular risk and disease occurrence [ 123 , 124 ]. It is obvious from these conventional treatment options that a more sustainable, much safer, and perhaps food-derived alternative therapy is warranted for treating or managing RA.…”
Section: Conventional Treatment Of Ramentioning
confidence: 99%
“…While phytocompounds have indeed been largely analyzed and under scrutiny, there are only a few, but promising reports on marine biology-derived compounds in the treatment of RA [26][27][28][29][30]. Very recently, a study using a marine extract in RA has shown a benefit effect on inflammatory pathways [31]. About 10 years ago, we had shown that a specific proprietary marine lipoprotein, fish DNA extracts and peptides-rich compound, LD-1227 (Caviarlieri, Lab-Dom, Switzerland) could significantly inhibit IL-1β-induced proliferation and inflammatory reactions by partly inhibiting the transcription factor NF-κB pathway in human chondrocytes ex-vivo derived from osteo-arthritis patients [32].…”
Section: Introductionmentioning
confidence: 99%